Surface analysis of latex and silicone pacifier nipples after exposure to acidic artificial saliva: a pilot study (Research, Society and Development, 2021)
Objective: To measure surface changes of pacifier nipples after immersion in acidic artificial saliva. Methods: Two types of pacifier nipples (latex and silicone) were selected. Five copies of each type were used. The protocol consisted of immersion in acidic artificial saliva (pH = 5.97) for 16 days. The nipples of the pacifier remained in direct contact with saliva in an individualized, opaque and closed container in a bacteriological incubator at 37ºC. The samples were examined before and after exposure to saliva through qualitative (based on images obtained in a 100 mm macro lens and three-dimensional images with 10% amplification obtained in the profilometry) and quantitative (roughness data obtained in non-contact 3D optical profilometry). Data were obtained in duplicate and analyzed using descriptive and inferential statistics. The findings were tested for normality (Shapiro-Wilk). Paired t-test or Wilcoxon was used to compare before and after roughness data. Results: In the image analysis, it was observed that only the surface of the latex pacifier's nipples showed an irregular appearance after exposure to saliva. In the quantitative evaluation, no differences were found between the roughness values before and after (p>0.05). Conclusion: This pilot study demonstrated qualitative changes in the surface of latex pacifiers. However, it was not able to demonstrate statistically significant differences for the roughness parameters before and after exposure to acidic artificial saliva in the nipples of latex and silicone pacifiers.